Interpersonal Communication and Long-Distance Relationships: A Narrative Study of Romantic Relationships Among Students Participating in Community Service Program in the Village of Ciledug Kulon - Desy Permatasari; Siti Khumayah; Farida Nurfalah (Green Publisher Indonesia, 2026)
The Community Service Program (KKN), which requires students to be physically separated from their partners, often results in relationships that are fraught with emotional challenges and communication limitations, making interpersonal communication an important element in maintaining the quality and meaning of those relationships during service. This research aims to understand the experiences and difficulties faced by students during KKN, especially how they manage interpersonal communication to sustain their relationships despite distance and differing schedules. This study uses a qualitative method with a narrative approach. The researcher collected data through in-depth interviews, observations, and structured documentation with three students who were undergoing KKN and had long-distance relationships, as well as from books and journals. The data were also supported by observations and personal files. The results show that students experience various complex feelings, such as longing, sadness, anxiety, and frustration, mainly due to changes in communication routines, heavy KKN workloads, and limited time. Their communication patterns shifted from emotional to more functional, using digital media such as WhatsApp for text messages and video calls. The main strategies for maintaining relationships are honesty, regular communication, conflict resolution, commitment, and mutual understanding. This study concludes that successful long-distance relationships during KKN require flexible communication skills, good emotional management, and a willingness to understand one's partner's limitations. It provides additional insights into interpersonal communication in specific situations and emphasizes the importance of flexibility and emotional intelligence in maintaining relationships under pressure.